Temporal and Spatial Variation in Vegetation and Its Influencing Factors in the Songliao River Basin, China - Lei Chang; Ying Li; Keyi Zhang; Jialin Zhang; Yuefen Li (Land, 2023)
As an important part of soil and water conservation, ecological stability, and climate regulation, vegetation is sensitive to climate change and human disturbance. At present, there is a lack of research on the dynamic changes to vegetation in river basins and sub-basins from a holistic and partial perspective, which limits our ability to understand the spatial heterogeneity of vegetation changes and their influencing factors. In this study, the spatial and temporal variations of vegetation and their influencing factors in the Songliao River Basin (SLB) from 2000 to 2020 were analyzed using Sen’s trend method, the Mann–Kendall test, the coefficient of variation method, and the Geodetector method. The results showed that the NDVI (normalized difference vegetation index) in the SLB exhibited an increasing trend of 0.003 yr−1, indicating that the vegetation was greening. In general, climatic factors and soil type were the dominant factors affecting the spatial differentiation of the NDVI in the SLB and sub-basin units. The interactions between the influencing factors were all enhanced, and the population density highlighted its influence on reflected vegetation changes. We also focused on analyzing the spatial differentiation of vegetation changes and influencing factors in the sub-basins. The research results provide a basis for the ecological restoration and stability of the basin.